PALATUM DURUM'U ETKİLEYEN SEPTUM DEVİASYONUNUN SİNUS MAXİLLARİS HACMİNE ETKİSİ - SAPMAZ, EMRAH (Fırat Üniveristesi, 2016)
Ağızdan solumaya neden olabilecek septum deviasyonu, adenoid vejetasyon gibi durumların fasial deformiteye neden olabileceği yapılan çalışmalarda rapor edilmiştir. Septumun kemik kısmının deviye olması yüz gelişimini etkileyerek fasial asimetriye neden olabilir. Yüz gelişiminde bu kadar etkili olan septumun, deviye olması durumunda palatum durumda açılanma yapıp yapmamasına bağlı olarak sinus maxillaris hacmine bir etkisinin olup olmadığını araştırmayı amaçladık. Yaşları 18 ile 60 arasında değişen 1568 hastanın koronal planda çekilen paranazal sinüs tomografileri incelendi. Toplam 402 tomografi görüntüsü çalışmaya dahil edildi. Sinus maxillaris'in kesite girdiği tüm bilgisayarlı tomografi görüntülerinin alanları planimetri yöntemi ile bilgisayar destekli program kullanılarak hesaplandı. Hesaplanan alanlar Cavalieri Prensibi ile hacme dönüştürüldü ve böylelikle her bir sinus maxillaris'in hacmi elde edildi. Aynı görüntülerde septum deviasyonu açısıyla palatum durum'daki açılanmalarda ölçülerek istatistiksel olarak karşılaştırıldı. Hem erkek hem kadın hasta grubunda palatum durumda açılanmaya yol açan veya açmayan septum deviasyonu kişilerin sinus maxillaris hacimlerinde farklılıklar tespit edildi. Deviasyonun olduğu taraftaki sinus maxillaris hacmi deviasyonun karşı tarafındaki sinus maxillaris hacminden daha küçük olarak hesaplandı ve her iki sinus maxillaris arasındaki hacim farkı istatistiksel olarak anlamlı idi (p<0.05). Septum deviasyonu açısı ile palatum durumda meydana gelen açılanma arasında pozitif bir korelasyon tespit edildi (0

Studies reported that the nasal septal deviation which may cause mouth breathing and the adenoid vegetation may result in facial deformity. Deviation of the bone of the nasal septum effecting facial growth may cause facial asymmetry. The aim of this study is to evaluate whether the nasal septum which has a significant role in facial growth has an effect on the volume of maxillary sinus or not in case of deviation depending on whether the hard palate is (palatal durum) deflected or not. Computed tomography scans of paranasal sinus of 1568 patients, ages ranging between 18 - 60, performed in coronal plane were examined. 402 computed tomography scans were included in the study. The areas of maxillary sinus viewed in slice in computed tomography scans were calculated by planimetry method using a computer-aided program. Calculated areas were converted into volume by Cavalieri Principle therefore, the volume of every maxillary sinus was calculated. With the same scans, the angle of nasal deviation and the curvature on the hard palate were calculated and compared statistically. Changes in the volumes of maxillary sinus of both female and male patients with the deviated nasal septum were formed by the septum which either deflects the hard palate or does not. The volume of the maxillary sinus on the deviated side was calculated less than the opposite side of the deviation and the difference between the volumes of both sinuses estimated statistically significant (p<0,05). A positive correlation was observed between the angle of nasal septal deviation and the curvature on the hard palate. Either the nasal septal deviation effects the hard palate or does not the maxillary sinus on the deviated side reduces its volume but it does not effect the total volume of maxillary sinus. People with the more difference between the volumes may experience facial asymmetry.
The effect of hard palate that deflects by nasal septal deviation on the volume of maxillary sinus
Keywords: Radyoloji ve Nükleer Tıp; Anatomi; Kulak Burun ve Boğaz